Extenders of the semantic model of the sentence in the light of A. Potebnjas theory of literature - Воробець, Олексій Дмитрович (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 1970)
The article analyzes the semantic potential of extenders as integral parts of the model of sentence which are characterized by totality and structured unity of the semantic meaning. It represents the peculiarities of extending components in the semantic structure of the sentence while taking into account obligatory tendencies of the A. Potebnjas theory of literature.